Unlocking growth: investigating asymmetry in the financial inclusion-growth nexus in financially inclusive Middle East economies - Xinyi, Shen; Qian, Huang; Nazar, Raima; Lee, Chin (Elsevier, 2024)
Financial inclusion is a crucial element of financial development that transmits cheap financial services to provide advantages to entire segments of society and stimulates economic growth. Our investigation evaluates the asymmetric financial inclusion-economic growth nexus in the top 10 financially inclusive Middle East nations (Israel, Oman, Iran, Qatar, Turkey, Saudi Arabia, Bahrain, Egypt, United Arab Emirates, and Kuwait). Earlier studies adopted panel data tools, which yielded typical outcomes on the association between financial inclusion and economic growth despite few economies did not indicate such a link individually. Conversely, the present work adopts Quantile-on-Quantile approach which can scrutinize time-series dependency among nations exclusively to give international, though country-specific, comprehension of the variables’ correlation. The outcomes show that financial inclusion boosts economic growth in our selected economies at numerous quantiles of data distribution. In addition, the results depict that the degree of asymmetry in the financial inclusion-economic growth nexus diverges by the nation. The outcomes highlight the critical need for governments and policymakers to prioritize financial inclusion and economic growth across various levels by emphasizing a strategic and comprehensive approach to ensure effective and sustainable growth.